SOSIALISASI PENGGUNAAN SOCIAL COGNITIVE CAREER THEORY (SCCT) UNTUK MEMBANTU SISWA DALAM MENETAPKAN PILIHAN JURUSAN AKUNTANSI DI PERGURUAN TINGGI - Yanto, Yanto; Aprilian, Rahil Imainul; Vebtasvili, Vebtasvili; Ridwan, Muhammad Qomaruddin (Universitas Mataram, 2024)
The background of this activity focuses on the low interest of students in continuing to higher education, particularly in the field of accounting. This is due to a lack of understanding regarding the diverse and promising career prospects in accounting, such as job stability, competitive salaries, and opportunities for growth. In addition, limited outreach about accounting careers has led students to overlook this field as a potential future career choice. This activity aims to increase students’ understanding and interest in accounting careers. The community service program at SMK Negeri 1 Sungailiat aims to enhance accounting students’ understanding and interest in pursuing higher education in accounting. Using the Social Cognitive Career Theory (SCCT) approach, this program provides career guidance through workshops, interactive discussions, and SCCT-based questionnaires that measure students' self-efficacy, outcome expectations, and career goals. The results of this activity show a significant increase in students’ understanding of the importance of higher education in expanding career opportunities in accounting. Additionally, there is an increase in students’ confidence in accounting career prospects, as reflected in the questionnaire results. Students now better understand various career benefits, such as job stability and opportunities for growth. Positive feedback from students also indicates that the Social Cognitive Career Theory (SCCT) approach is effective in helping them make better career decisions. Therefore, this activity successfully motivates students to consider accounting as a career choice. In conclusion, SCCT-based career guidance helps students confidently choose accounting as their major. Recommendations are made to extend the duration of interaction and strengthen career guidance programs so that students receive continuous support in planning their education and future careers.